IMPLIKASI PERMAINAN TRADISIONAL â€œMAJJEKA CAPENGâ€ DALAM MENGEMBANGKAN MOTORIK KASAR ANAK USIA DINI - Basri, Hasan (Institut Agama Islam Negeri Bone, 2022)
Attention to the growth and development of early childhood is fundamental and strategic in the development of human resources. Physical development of early childhood can be marked by the development of gross and refined motor. This paper discusses the implication of the traditional game â€œMajjeka Capengâ€ in developing gross motor for early childhood. â€œMajjeka Capengâ€ is a traditional game for Bugis Makassar children from South Sulawesi. Through literature review using content analysis techniques, it seems that the game can develop childrenâ€™s physical skills, and can get acquainted with their environment without the help of others.